Semi-quantitative determination of active sites in heterogeneous catalysts for photo/electrocatalysis - Ren, Jing; Chi, Haoyuan; Tan, Ling; Peng, Yung-Kang; Li, Guangchao; Meng-Jung Li, Molly; Zhao, Yufei; Duan, Xue (Journal of materials chemistry. A, Materials for energy and sustainability, 2023)
Catalysis is a widely applied process due to its predominant role in the chemical industry. Developing highly active exposed facets via defect engineering is considered to be the most promising strategy for optimizing the electrical and optical properties of catalysts to improve their catalytic activity. Therefore, quantitative determination and calculation of the concentration of defect structures related to the highly exposed active crystal plane provided an efficient route for elucidating the catalytic active sites, and has attracted increasing attention. This work not only summarizes the existing defect characterization methods and the calculation methods of defect concentrations reported in recent years but also proposes a semi-quantitative method based on X-ray absorption fine structure (XAFS) and related methods for the determination and classification of active sites related to the active surface, which can be applied for the semi-quantitative calculation of defect concentrations in widely used metals and metal oxides. In addition, we emphasize the deficiencies of current defect concentration quantitative methods and look forward to the future development of defect characterization methods under working conditions. This review further reveals the structure-activity relationship between the content of active sites and the reaction performance. This review focuses on exploring the defect active sites by determining the location and type and semi-quantitative calculation of defect concentrations by a variety of representational methods.